Identification of Type VI Secretion Systems Effector Proteins That Contribute to Interbacterial Competition in Salmonella Dublin - Amaya, Fernando A.; Blondel, Carlos J.; Barros-Infante, María F.; Rivera, Dácil; Moreno-Switt, Andrea I.; Santiviago, Carlos A.; Pezoa, David (Frontiers in Microbiology, 2022)
The Type VI Secretion System (T6SS) is a multiprotein device that has emerged as an important fitness and virulence factor for many Gram-negative bacteria through the injection of effector proteins into prokaryotic or eukaryotic cells via a contractile mechanism. While some effector proteins specifically target bacterial or eukaryotic cells, others can target both types of cells (trans-kingdom effectors). In Salmonella, five T6SS gene clusters have been identified within pathogenicity islands SPI-6, SPI-19, SPI-20, SPI-21 and SPI-22, which are differentially distributed among serotypes. Salmonella enterica serotype Dublin (S. Dublin) is a cattle-adapted pathogen that harbors both T6SSSPI-6 and T6SSSPI-19. Interestingly, while both systems have been linked to virulence and host colonization in S. Dublin, an antibacterial activity has not been detected for T6SSSPI-6 in this serotype. In addition, there is limited information regarding the repertoire of effector proteins encoded within T6SSSPI-6 and T6SSSPI-19 gene clusters in S. Dublin. In the present study, we demonstrate that T6SSSPI 6 and T6SSSPI-19 of S. Dublin CT_02021853 contribute to interbacterial competition. Bioinformatic and comparative genomic analyses allowed us to identify genes encoding 3 candidate antibacterial effectors located within SPI-6 and 4 candidate effectors (including a potential trans-kingdom effector) located within SPI-19. Each antibacterial effector gene is located upstream of a gene encoding a hypothetic immunity protein, thus conforming an effector/immunity (E/I) module. Of note, the genes encoding these effectors and immunity proteins are widely distributed in Salmonella genomes, suggesting a relevant role in interbacterial competition and virulence. Finally, we demonstrate that E/I modules SED_RS01930/SED_RS01935 (encoded in SPI-6), SED_RS06235/SED_RS06230 and SED_RS06335/SED_RS06340 (both encoded in SPI-19) contribute to interbacterial competition in S. Dublin CT_02021853.